Mapping sheep to human brain: The need for a sheep brain atlas - Banstola, Ashik; Reynolds, John N. J. (Frontiers in Veterinary Science, 2022)
A brain atlas is essential for understanding the anatomical relationship between neuroanatomical structures. Standard stereotaxic coordinates and reference systems have been developed for humans, non-human primates and small laboratory animals to contribute to translational neuroscience research. Despite similar neuroanatomical and neurofunctional features between the sheep and human brain, little is known of the sheep brain stereotaxy, and a detailed sheep atlas is scarce. Here, we briefly discuss the value of using sheep in neurological research and the paucity of literature concerning the coordinates system during neurosurgical approaches. Recent advancements such as computerised tomography, positron emission tomography, magnetic resonance imaging, functional magnetic resonance imaging and diffusion tensor imaging are used for targeting and localising the coordinates and brain areas in humans. Still, their application in sheep is rare due to the lack of a 3D stereotaxic sheep atlas by which to map sheep brain structures to its human counterparts. More recently, a T1- and T2-weighted high-resolution MRI 3D stereotaxic atlas of the sheep brain has been generated, however, the journey to create a sheep brain atlas by which to map directly to the human brain is still uncharted. Therefore, developing a detailed sheep brain atlas is valuable for the future to facilitate the use of sheep as a large animal experimental non-primate model for translational neurological research.